2018
DOI: 10.1097/tp.0000000000001956
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Monotherapy by Rituximab Without Additional Desensitization in ABO-incompatible Living-Donor Liver Transplantation

Abstract: Pretransplant rituximab without additional treatments yielded satisfactory outcomes comparable to that with additional treatments, such as PP and LI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…In the present study, ABO‐incompatible graft usage in the XS group was higher than in the S group and was more often used in the context of ALF for infants in both the XS and S groups with good outcomes, and no desensitization manipulations were used. Both pediatric and adult ABO‐incompatible LT survival has improved markedly and has become comparable to ABO‐compatible LT on the introduction of rituximab prophylaxis before LT . However, infants are able to accept ABO‐incompatible grafts without desensitization therapy because the immune system is still developing, which can be verified by confirming low levels of anti‐A and anti‐B antibody titers (<1/8).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, ABO‐incompatible graft usage in the XS group was higher than in the S group and was more often used in the context of ALF for infants in both the XS and S groups with good outcomes, and no desensitization manipulations were used. Both pediatric and adult ABO‐incompatible LT survival has improved markedly and has become comparable to ABO‐compatible LT on the introduction of rituximab prophylaxis before LT . However, infants are able to accept ABO‐incompatible grafts without desensitization therapy because the immune system is still developing, which can be verified by confirming low levels of anti‐A and anti‐B antibody titers (<1/8).…”
Section: Discussionmentioning
confidence: 99%
“…Based on this policy, we have used a protocol based on the administration of rituximab (patients who were 2 years or older), tacrolimus, steroids, and MMF without PE, local infusion, and splenectomy since 2010 in ABOi LDLT. 25 …”
Section: Discussionmentioning
confidence: 99%
“…16 It has been previously reported that the target of pre-transplant antibody ABO-titer values following plasmapheresis were less than 1:8, 1:16, 1:32 or 1:64 to prevent posttransplant AMR. 14 The target titer differs markedly by center and a standard target titer has not yet been established.…”
Section: Plasmapheresis or Total Plasma Exchangementioning
confidence: 99%
“…24 Since the rituximab era, many centers are now trying to simplify the protocol, and avoid splenectomy, local graft infusion, IVIG, and plasmapheresis. [14][15][16][17][18][19][20]…”
Section: Rituximabmentioning
confidence: 99%